Economic Growth and Environmental Quality: A Study on Mineral-Rich Provinces in Indonesia - Ramadanti, Sarindang Suci; Azwardi, Azwardi; Subardin, Muhammad (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: This research focuses on Indonesia's mineral-rich provinces and offers originality through its comprehensive analysis of the bidirectional relationship between economic growth and environmental quality, using the Environmental Quality Index (EQI). Research Objectives: This study examines the relationship between economic growth and environmental quality in the Mineral Economy Provinces of Indonesia.Research Methods: The data used in this research is secondary data from 2015 to 2022. The analysis method employed is the simultaneous equation model using Two Stage Least Squares (2SLS).Empirical Results: The results show that in model 1, economic growth is significantly influenced by exogenous variables such as the environmental quality index, energy consumption, revenue sharing funds, investment, and population. In model 2, environmental quality is significantly influenced by exogenous variables such as GDP, mining output, energy consumption, and forest. Good environmental quality can enhance economic growth. Conversely, increased Economic growth can degrade environmental quality.Implications: The study's findings suggest that policymakers in Indonesia's mineral economy provinces should prioritize sustainable development to balance economic growth with environmental preservation.JEL Classification: Q43, Q50, Q56